Nursing Home Residents with Dementia Experience Better End‐of‐Life Care and Outcomes in Nursing Homes with Alzheimer's Special Care Units. (20th August 2020) - Orth, J.; Li, Y.; Simning, A.; Zimmerman, S.; Temkin‐Greener, H.
Abstract : Research Objective: Nursing homes (NHs) are critical end‐of‐life (EOL) care settings for 70% of Americans dying with Alzheimer's disease/related dementia (ADRD). Associations between facility‐level organization of care, including presence of Alzheimer's special care units (ASCUs), and EOL care quality in NHs are unclear. Our objective was to examine variations in EOL care/outcomes (in‐hospital/NH death, death with pressure ulcers, potentially avoidable hospitalizations (PAHs), and hospice use in the last 90 days of life) among residents who died with mild, moderate, or severe ADRD in NHs with/without ASCUs. Study Design: We used descriptive analyses and multivariate logistic regression models, adjusting for resident, NH, county, and state‐level factors, to examine associations between EOL care/outcomes and presence of ASCUs among NH decedents with ADRD. Population Studied: We used CY2016‐2017 national Medicare claims data and the Minimum Data Set (MDS) to identify long‐stay NH residents with ADRD who died in 2017. The sample included residents who died in a NH or hospital shortly following NH discharge, were not comatose, and were at least 65 years old at time of death. We used ICD‐10 diagnosis codes and the cognitive function scale to determine ADRD presence and severity. Medicare claims, the MDS, and several public data sets were used to assess EOL quality and identify resident, NH, and market‐level covariates. The study sample included 191 435 decedents with ADRD from 14 618 NHs. Principal Findings: As severity of ADRD increased, adjusted rates of in‐hospital death and PAHs decreased (17.2%‐6.4% for in‐hospital death; 12.0%‐7.3% for PAHs; P ‐values:< 0.001), while adjusted rates of dying with pressure ulcers and hospice use increased (8.4%‐13.7% for deaths with pressure ulcers; 23.4%‐39.7% for hospice use; P ‐values:< 0.001). Presence of ASCUs lowered the adjusted rate of in‐hospital death (3.7%, 2.2%, 2.5%; P ‐values:< 0.001), dying with pressure ulcers (0.6%, 2.1%, 4.3%; P ‐values:< 0.001), and PAHs (1.8%, 1.5%, 2.3%; P ‐values:< 0.001) among decedents with mild, moderate, and severe ADRD, respectively. Adjusted rates of hospice use were not as clinically significant or consistent across decedents with differing levels of ADRD severity. Decedents in for‐profit NHs with ASCUs had higher odds of in‐hospital death (OR:1.17; P ‐value: 0.032) and hospice use (OR:1.19; P ‐value: 0.030). In NHs with ASCUs, higher skilled nurse staffing was associated with lower odds of PAHs (OR:0.07; P ‐value: 0.002) and hospice use (OR:0.16; P ‐value:< 0.001). In more competitive NH markets, presence of ASCUs was associated with higher odds of hospice use (ORs: 1.74, 1.33; P ‐values:< 0.001, 0.035). Conclusions: NH decedents with ADRD residing in NHs with ASCUs were consistently more likely to die in NHs rather than in hospital and had fewer pressure ulcers and PAHs at EOL. Implications for Policy or Practice: Our findings suggest that presence of ASCUs may create environments in which better outcomes are possible for residents dying with ADRD. However, because there is no definition as to what constitutes ASCUs, it is difficult to identify specific dimensions promoting better care. Future research to understand NH practice/care processes associated with presence of ASCUs is needed to identify possible interventions/policy initiatives to increase ASCU presence. Primary Funding Source: Agency for Healthcare Research and Quality.